Pollution and the choice of where to work and live within Mexico City - Matías Fontenla; M. Ben Goodwin; Fidel Gonzalez (Latin American Economic Review, 2019)
Global air pollution continues to increase across the world, and Mexico City is one of the most polluted cities in the western hemisphere. This paper considers the tradeoff between wages, housing characteristics, and air quality in the conjoint decision of where a household decides to live and work. We estimate compensating differentials using a three-stage least squares (3SLS) instrumental variable approach that accounts for the simultaneous nature of the housing and wage markets. To address endogeneity, we capitalize on the localized relationship between air pollution and rainfall. We assemble a dataset for Mexico City which includes the actual transacted value of the house, house features, household socioeconomic characteristics, particulate matter pollution (PM10) concentrations, and rainfall. Our results indicate that the average household needs to be compensated by approximately US 1007.54 per year to tolerate a 1 µg/m3 increase in PM10. Our estimates are on the higher end of previous studies. If estimates under-represent the value of clean air, then this discourages government policy aimed at mitigating pollution, with all its health and quality of life implications.
Keywords: O1; Q5; R2; 330; Particulate matter (PM10); Valuation of air quality; Wage-hedonic models; Residential sorting; Compensating diferential; Marginal willingness to pay; Mexico; Latin America